2010
DOI: 10.1159/000316942
|View full text |Cite
|
Sign up to set email alerts
|

Connexin Channel-Dependent Signaling Pathways in Inflammation

Abstract: Inflammation is a highly regulated process with common but also specific characteristics in each tissue affected. Recruitment of leukocytes from the blood to the injured tissue is an important early step in the inflammatory cascade. This review highlights the role of connexins (Cxs) in the regulation of both acute and chronic inflammatory processes. Cxs form gap junction channels that provide a cytoplasmic continuity between adjacent cells allowing the intercellular exchange of ions and metabolites. Their stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 230 publications
(169 reference statements)
4
66
0
Order By: Relevance
“…For this, it is essential to use a purified and reconstituted preparation of HCs where there is no possibility of Ca 2ϩ transport through parallel unidentified pathways. Our results support previous interpretations that suggested a role of Ca 2ϩ fluxes through GJCs and HCs in physiological and pathophysiological conditions (17,21,(25)(26)(27)(28). Ca 2ϩ permeability is relatively high, similar to that for Na ϩ .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For this, it is essential to use a purified and reconstituted preparation of HCs where there is no possibility of Ca 2ϩ transport through parallel unidentified pathways. Our results support previous interpretations that suggested a role of Ca 2ϩ fluxes through GJCs and HCs in physiological and pathophysiological conditions (17,21,(25)(26)(27)(28). Ca 2ϩ permeability is relatively high, similar to that for Na ϩ .…”
Section: Discussionsupporting
confidence: 91%
“…Although most cells have fewer HCs than GJCs at the plasma membrane, the much higher extracellular [Ca 2ϩ ] suggests that HCs can have a significant role in Ca 2ϩ influx, at least under certain circumstances (17,21,(25)(26)(27)(28) or in disease-causing mutants that display higher Ca 2ϩ permeability (G45E mutant associated with keratitis ichthyosis deafness syndrome) (29). In summary, our results showed that Cx26 HCs are permeable to Ca 2ϩ and suggest that HCs can be a pathway for Ca 2ϩ influx into cells under conditions such as ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of purinergic signaling to atherosclerosis has been illustrated by a series of genetic mouse models (1551). Monocyte Cx37 serves as a hemichannel for release of ATP (see FIGURE 14).…”
Section: A Purinergic Signalingmentioning
confidence: 99%
“…However, gap junctions have been shown to be disrupted by inflammation (21) and oxidative stress (27). Paired connexins (connexons) play an important role in gap-junctional intercellular communication while unpaired connexins allow communication between the cytosol and extracellular environment.…”
mentioning
confidence: 99%